Critique of radical religious paradigm: an epistemological analysis from principles of Islamic thought - Ade Dedi Rohayana; Muhammad Jauhari Sofi (Indonesian Journal of Islam and Muslim Societies, 2021)
As one important factor enabling Islamophobia, radicalism has been a global issue endangering personal safety and public security. It is strongly associated with incorrect understanding of religious doctrines. This paper aims to present a critique of religious paradigm promoted by the radical groups from principles of Islamic thought (usul fiqh) perspective. Using epistemological analysis to uncover the nature of their religious understanding and its justification, this study argues that radical religious paradigm is characterized with monolithic, textual, and rigid interpretation of the sacred texts. According to the radical groups, the sources of Islamic laws or teachings are restricted to only the Quran and the hadith, leaving no space for alternative interpretations. They do not give a place for ra’yu (reason) in determining the laws or teachings. In the other hands, usul fiqh maintains that the sources of the Islamic laws or teachings are not restricted to only the two said sources; it also gives a place for ra’yu (reason). From usul fiqh perspective, the sources can also be found in the form of isyarah (signalling) and ruh (spirit) of the Quran and the hadith. In this sense, usul fiqh refuses the literal interpretation proposed by the radical groups since not all of the texts in the Quran and the hadith can be understood literally.